Market forces at play: the impact of audit market concentration and firm market power on audit fees / Natasha Aritha Saphirra, Wiwi Idawati and Eddy Susanto - Saphirra, Natasha Aritha; Idawati, Wiwi; Susanto, Eddy (Universiti Teknologi MARA Selangor, 2023)
The objective of this study is to examine the impact of Audit Market Concentration and Audit Firm Market Power on Audit Fees in nonfinancial firms listed on the Indonesia Stock Exchange between 2017 and 2020. The sample of 194 companies was chosen through purposive sampling. The independent variable, Audit Market Concentration, was measured using the Herfindahl Hirschman Index (HHI), and Audit Firm Market Power was measured using the absolute smallest difference in the market share value of an Audit Firm and its closest competitors. The market share was calculated using Audit Fee proxies that were summed based on the IDX Industrial Classification (IDX-IC). Our findings reveal that the market structure in Indonesia is a tight oligopoly, and the audit market conditions in the country are highly concentrated. Our results suggest that Audit Market Concentration has no effect on Audit Fees, while Audit Firm Market Power has a positive influence on Audit Fees.